Analisa Perilaku Kepatuhan Pajak - Mulyana, Grace (Jurnal Akuntansi, 2024)
This research aims to analyze the influence of motivation, social norms, and trust in the government on tax compliance. The sample research method used in this research is convenience sampling, namely sampling which is carried out randomly by considering the speed of access that can be reached by the researcher. The regression model used in this research is a multiple linear regression model with the help of IBM SPPS 24. The research results show that motivation, social norms and trust in the government have a significant positive effect on tax compliance. Keywords: Motivation, social norms, trust in government, tax compliance